Analisis Optimalisasi Penggunaan Microsoft Excel dalam Sistem Accouting untuk Penyusunan Laporan Keuangan guna Mendukung Asumsi Going Concern - Annisa, Annisa; Masyhuri, Masyhuri (Journal of Economic and Business Advancement, 2026)
This study aims to analyze the optimization of Microsoft Excel usage in accounting systems for the preparation of financial statements to support the going concern assumption. The method used is a qualitative approach based on a literature review, employing descriptive-interpretive analysis through thematic synthesis of relevant literature. The results of the study indicate that the optimization of Excel features such as logical functions, automatic calculations, and structured templates can enhance the efficiency, accuracy, and timeliness of financial statement preparation. The quality of the information produced contributes to the transparency and credibility of the reports used in assessing business continuity. Excel supports the analysis of financial indicators such as leverage and financial distress that influence the going concern opinion. The application of Excel still requires internal controls to minimize input errors. Excel serves as a strategic tool in improving the quality of financial reporting and supports a more systematic evaluation of business continuity in modern accounting practice.